2014
DOI: 10.4028/www.scientific.net/amm.507.353
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation on the Strength Characteristics of Cement-Treated Base

Abstract: Cement-Treated Base (CTB) is a non-conventional method used in road bases materials to improve its engineering properties due to the hardening of cement when moisture is present and extends the period of curing times. This study investigates the effects of cement additive on properties of base layer using laboratory mechanistic evaluation of stabilized soil mixtures. Laboratory tests conducted were Unconfined Compressive Strength (UCS), Indirect Tension test for Resilient Modulus (ITRM) and Flexure Strength (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 10 publications
0
35
0
3
Order By: Relevance
“…These include ambient air temperature, relative humidity, type of cement used, and concentration of cement used. Guthrie and Reese [34] found that the relative strength is sensitive to the previously mentioned factors, while the relative compaction is not. Faster wind speed, higher air temperature, lower relative humidity and longer delay in compaction commonly result in a poor strength.…”
Section: Stabilization Using Cementmentioning
confidence: 99%
“…These include ambient air temperature, relative humidity, type of cement used, and concentration of cement used. Guthrie and Reese [34] found that the relative strength is sensitive to the previously mentioned factors, while the relative compaction is not. Faster wind speed, higher air temperature, lower relative humidity and longer delay in compaction commonly result in a poor strength.…”
Section: Stabilization Using Cementmentioning
confidence: 99%
“…By maintaining a lower thickness, i.e. by avoiding thickness increase, an engineer enables faster construction work and thus better use of valuable resources [1]. Furthermore, a stiffer base reduces deflections due to heavy traffic loads, thereby extending pavement life and reducing maintenance costs.…”
Section: Introductionmentioning
confidence: 99%
“…In FDR, the most used test to verify that material was manufactured correctly is the unconfined compressive strength (UCS) test at short-term [10,[27][28][29][30]. But, in order for a better long-term characterization, it is necessary to perform flexural strength tests, and, more specifically, the four-point flexural beam test [8,[31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…This FS test is carried out using prismatic specimens and manufacturing them requires a high level of qualification and experience within the testing team [10,39]. This is the main reason for usually estimating their behavior from standardized tests, such as the unconfined compressive strength and the indirect tensile strength (ITS) tests [31,[40][41][42]. For this reason, the method used in this research is the one proposed by the University of Burgos [33].…”
Section: Introductionmentioning
confidence: 99%